2002
DOI: 10.1086/324544
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Emission Processes in Radio Jets

Abstract: The emission processes responsible for the observed X-rays from radio jets are commonly believed to be non-thermal, but in any particular case, it is unclear if synchrotron emission or one or more varieties of inverse Compton emission predominates. We present a formulation of inverse Compton emission from a relativistically moving jet ("IC/beaming") which relies on radio emitting synchrotron sources for which the energy densities in particles and fields are comparable. We include the non-isotropic nature of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
227
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(236 citation statements)
references
References 33 publications
8
227
1
Order By: Relevance
“…Previous analyses have demonstrated that the X-ray jet emission of M87 is not thermal emission (Wilson & Yang 2002;Marshall et al 2002;Biretta, Stern, & Harris 1991), is not SSC emission (ibid), and is not IC/CMB emission because of the large values of G and small angles to the line of sight required (Harris & Krawczynski 2002). The X-ray spectra of the knots 12 We obtained a short observation in 2002 October as a result of an ad hoc proposal.…”
Section: A "Modest Beaming" Synchrotron Model For Hst-1mentioning
confidence: 89%
See 2 more Smart Citations
“…Previous analyses have demonstrated that the X-ray jet emission of M87 is not thermal emission (Wilson & Yang 2002;Marshall et al 2002;Biretta, Stern, & Harris 1991), is not SSC emission (ibid), and is not IC/CMB emission because of the large values of G and small angles to the line of sight required (Harris & Krawczynski 2002). The X-ray spectra of the knots 12 We obtained a short observation in 2002 October as a result of an ad hoc proposal.…”
Section: A "Modest Beaming" Synchrotron Model For Hst-1mentioning
confidence: 89%
“…We performed these calculations for eight values of d between 1 and 16. For converting various quantities to the jet frame and back, we used expressions from the Appendix of Harris & Krawczynski (2002). The results for representative values of d are shown in Table 1.…”
Section: A "Modest Beaming" Synchrotron Model For Hst-1mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we find that for z ¼ 0:2, U 0 CMB /U 0 B $ 3 ; 10 À3 (model 1) and 0.1 (model 2), where U 0 CMB is the energy density of the cosmic microwave background calculated in the rest frame of the jet, assuming À ¼ 5 and a viewing angle of 30 (Harris & Krawczynski 2002). Thus, synchrotron radiation is again the dominant radiation mechanism.…”
Section: Discussionmentioning
confidence: 78%
“…If the X-ray emission of IGR J21247+5058 comes indeed from a radio galaxy, then it should originate in the core and/or in the first secction of the jet, where synchrotron or inverse Compton emission processes dominate (Harris & Krawczynski 2002). This source could be a similar case to 3C 273 (Marshall et al 2001), where the detected X-rays fade along the jet.…”
Section: Further Commentsmentioning
confidence: 98%